Quality as a Driver of Sustainable Agricultural Value Chains: The Case of the Relationship Coffee Model. (7th February 2018) - Hernandez‐Aguilera, J Nicolas; Gómez, Miguel I; Rodewald, Amanda D; Rueda, Ximena; Anunu, Colleen; Bennett, Ruth; van Es, Harold M
Abstract: Specialty coffee markets that recognize coffee‐quality price premiums can improve business conditions for smallholders and promote agro‐ecological practices. We studied the Relationship Coffee Model (RCM), a business model that supports long‐term partnerships between coffee buyers and smallholders based on product quality. We examined how biophysical conditions and production practices affect smallholders' ability to participate in this model. Furthermore, we considered common unobservable variables driving growers' participation such as farm soil quality and connection to social networks. In turn, we evaluated key environmental, socio‐economic and technological outcomes, including tree and bird population diversity. Our estimations indicated that RCM participants employed more sustainable resource management practices, had better access to credit and were more informed and optimistic about the coffee business. However, we did not find significant farm‐gate price differences. Increased adoption of organic farming and shade‐grown systems to elevate coffee quality can stimulate sustainable business strategies. Copyright © 2018 John Wiley & Sons, Ltd and ERP Environment